SOCIOCULTURAL DEVELOPMENT AND INTERCULTURAL AWARENESS TO IMPROVE THE SECOND LANGUAGE ACQUISITION COMPETENCE FOR LEARNERS - Neldawati Neldawati; Irwandi Irwandi (Adisam Publisher, 2025)
This journal investigates the critical roles that intercultural awareness and sociocultural development play in enhancing learners' second-language acquisition (SLA) proficiency. It explores the complex interactions between social, cultural, and environmental elements and language development and competency. The study examines how social interactions, community immersion, and cultural sensitivity substantially impact second language learners' acquisition of the language by drawing on previous research and theoretical frameworks. It also critically examines how intercultural competence affects learners' identities, promotes flexibility, and aids in effective communication within the framework of language learning. The journal also looks at instructional strategies that incorporate sociocultural and intercultural components into language instruction, with a focus on using real materials and cross-cultural interactions to improve students' language and cultural competency. This publication emphasizes the value of sociocultural and intercultural elements in maximizing the competency and overall development of students pursuing second language acquisition by examining these characteristics.